(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strategic Decision-Making (SDM) is the process of charting a path focused on long-term priorities and a vision for an organization. SDM is the fundamental responsibility of Top Management teams (TMT) and is considered as central to an organization’s survival and growth. An appropriate ongoing strategic decision making facilitates an organization to align its operations with external dynamic conditions, contributing to retaining their competitive position. Most often decision making is viewed as a rational or bounded rational principle with the assumption of decision makers having the best actions to choose from. This principle does not take into consideration the challenges and difficulties associated with finding the best options. We conceptually apply Computational Complexity Theory (CCT) to assess the challenges associated with decision making. We argue there is scope to build further on the strategic decision-making research domain integrating the rational and bounded rationality principle-based theories with multidisciplinary aspects including computational complexity theories to better explain all aspects of decision-making process.